Kvasir-Capsule, a video capsule endoscopy dataset - Pia H. Smedsrud (Nature Portfolio, 2021)
Measurement(s) Gastrointestinal Tract • gastrointestinal system disease Technology Type(s) Capsule Endoscope • visual assessment of in vivo video recording Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment alimentary part of gastrointestinal system Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14178905